Politics in the Formulation of Educational Policy as a Form of Power in Public Policy - Sya’roni; Mulyadi; Masduki Duryat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This paper is a qualitative study based on literature review that explores the political dynamics in the formulation of education policy as a manifestation of power in public policy. Education is not merely a technical-administrative process, but rather a strategic field where ideological contestation, vested interests, and power hegemony take place. Employing a critical theoretical approach, particularly Michel Foucault’s concept of power-knowledge relations and Antonio Gramsci’s theory of hegemony, this study analyzes how education policies are designed, negotiated, and implemented within non-neutral power structures. The findings reveal that education policy often serves as a legitimizing tool for dominant power, shaping educational narratives, values, and practices aligned with elite interests. The political process involving state actors, political elites, bureaucracies, and international institutions plays a decisive role in directing the trajectory and content of national education policy. Thus, education policy is not merely a public policy product but also a mechanism of power to govern, discipline, and produce citizen-subjects according to specific ideological constructions. This study recommends the cultivation of critical awareness in reading education policymaking processes, so that the resulting policies truly uphold social justice, emancipation, and structural liberation.